Formation of a Composite Albian–Eocene Orogenic Wedge in the Inner Western Carpathians: P–T Estimates and 40Ar/39Ar Geochronology from Structural Units - Putiš, M.; Nemec, O.; Danišík, Martin; Jourdan, Fred; Soták, J.; Tomek, Č.; Ružička, P.; Molnárová, A. (MDPI, 2021)
The composite Albian–Eocene orogenic wedge of the northern part of the Inner Western Carpathians (IWC) comprises the European Variscan basement with the Upper Carboniferous–Tri-assic cover and the Jurassic to Upper Cretaceous sedimentary successions of a large oceanic–conti-nental Atlantic (Alpine) Tethys basin system. This paper presents an updated evolutionary model for principal structural units of the orogenic wedge (i.e., Fatricum, Tatricum and Infratatricum) based on new and published white mica40Ar/39Ar geochronology and P–T estimates by Perple_X modeling and geothermobarometry. The north-directed Cretaceous collision led to closure of the Jurassic–Early Cretaceous basins, and incorporation of their sedimentary infill and a thinned basement into the Albian–Cenomanian/Turonian accretionary wedge. During this compressional D1 stage, the subautochthonous Fatric structural units, including the present-day higher Infratatric nappes, achieved the metamorphic conditions of ca. 250–400 °C and 400–700 MPa. The collapse of the Albian–Cenomanian/Turonian wedge and contemporary southward Penninic oceanic subduc-tion enhanced the extensional exhumation of the low-grade metamorphosed structural complexes (D2 stage) and the opening of a fore-arc basin. This basin hemipelagic Coniacian–Campanian Couches-Rouges type marls (C.R.) spread from the northern Tatric edge, throughout the Infratatric Belice Basin, up to the peri-Pieniny Klippen Belt Kysuca Basin, thus tracing the south-Penninic sub-duction. The ceasing subduction switched to the compressional regime recorded in the trench-like Belice “flysch” trough formation and the lower anchi-metamorphism of the C.R. at ca. 75–65 Ma (D3 stage). The Belice trough closure was followed by the thrusting of the exhumed low-grade metamorphosed higher Infratatric complexes and the anchi-metamorphosed C.R. over the frontal un-metamorphosed to lowest anchi-metamorphosed Upper Campanian–Maastrichtian “flysch” sediments at ca. 65–50 Ma (D4 stage). Phengite from the Infratatric marble sample SRB-1 and meta-marl sample HC-12 produced apparent40Ar/39Ar step ages clustered around 90 Ma. A mixture interpretation of this age is consistent with the presence of an older metamorphic Ph1 related to the burial (D1) within the Albian–Cenomanian/Turonian accretionary wedge. On the contrary, a younger Ph2 is closely related to the late-to post-Campanian (D3) thrust fault formation over the C.R. Celadonite-enriched muscovite from the subautochthonous Fatric Zobor Nappe meta-quartzite sample ZI-3 yielded a mini-plateau age of 62.21 ± 0.31 Ma which coincides with the closing of the Infratatric foreland Belice “flysch” trough, the accretion of the Infratatricum to the Tatricum, and the formation of the rear subautochthonous Fatricum bivergent structure in the Eocene orogenic wedge.